Relative abundance of some wheat and barley insects at Al–Mareg region - Al – Ali, A. M. –; Hamednalla, H.; El–Gheriani , I.; Ekaram, H. (Al-Mukhtar Journal of Sciences, 1999)
Results showed that most of insect species which attacked wheat and barley at Mareg region appeared during the next half of march in a high number and decreased gradually till the end of May. Pachytychius hordie Brulle appeared and disappeared during the first half of stuied period, but Aphid sp. Was appeared and disappeared during the second half of studied period. The most abundant insect species in wheat and barley plots were Sminthurus sp., Aphis spp., P. hordie and Thrips spp. Pachytychius hordie and Aphid spp. were found in wheat plots more than barley plots as a ratio of (4\1) and (1.8 : 1.2) respectively, whereas sminthurus sp. And Thrips spp. Found in barely plots more than wheat plots as a ratio of (5 : 1) and (2 : 1) respectively.